KINERJA APARATUR PEMERINTAH DALAM PELAYANAN PUBLIK DI BIDANG PEMBUATAN E-KTP DI KECAMATAN BELIMBING KABUPATEN MELAWI - Theonardus Aririski E.42009060 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This essay entitled "Performance of Government Personnel Services in e-ID card Creation In District Belimbing, Melawi regency". Essay writing is intended to describe the implementation of the Government Performance Accountability Administrative District Belimbing, Melawi regency in Public Service in the manufacture of e-ID card. The essay is based on the issues raised in the employee performance related agencies, such concerns about the accountability of employees. These results indicate that employee accountability In District Belimbing is good enough viewed from the level of honesty, objectivity, transparency and innovative capabilities  further accountability is optimal employee can be seen from the achievement of goals or objectives related agencies, and the work produced satisfactory employee of the creation of e-ID card. The limited facilities and infrastructure owned by an obstacle in completing the work, but these obstacles can be overcomeKeywords: Performance Personnel, Public Service, Accountability